(untitled) (Bangladesh Medical Journal, 2021)
Hyperuricaemia is now an established factor to cause oxidative stress, insulin resistance and systemic inflammation. So it is likely that hyperuricemia might be involved in hepatic necroinflammation and destruction which are the common underlying pathophysiology of cirrhosis. On the other hand, as uric acid is the end product of cellular degradation, increased hepatocyte destruction due to any etiology increases the level of serum uric acid which might further aggravate hepatic necroinflammation, cirrhosis and complications. The aim of this study is to assess serum uric acid concentrations in patients of cirrhosis of liver and its relation with cirrhosis of different etiology, disease severity and liver enzymes. This cross sectional observational study was carried out in the Department of Gastroenterology, Banghabandhu Sheikh Mujib Medical University, Bangladesh during the period of September 2015 to October 2016. A total of 220 diagnosed cases of cirrhosis of liver due to any cause from inpatient and outpatient Department of Gastroenterology were enrolled as the study population. Serum uric acid level was measured in each patient and its relationship with different etiology of cirrhosis, severity of cirrhosis and liver enzymes were assessed. The mean age was found to be 47.8 ± 14.6 years and male: female ratio was 1.9:1. Majority patients (52.3%) belonged to Child-Turcotte-Pugh Class C. The mean (±SD) value of serum uric acid was 6.19 (±3.25mg/dl) and hyperuricemia (>7 mg/dl) was detected in 27.73% patients. Among all etiologies of cirrhosis, the higher mean (±SD) level of serum uric acid was found in Non-alcoholic Fatty Liver Disease (19.54 ±2.20 mg/dl). There was positive correlation of serum uric acid with liver enzymes. Mean serum uric acid level increased gradually as the cirrhotic patients progressed to higher CTP classes and there was positive correlation of serum uric acid with liver enzymes. It requires further large scale multicenter studies with increased sample size & prolong follow-up to establish serum uric acid as a risk factor of cirrhosis of liver. Bangladesh Med J. 2021 January; 50(1) : 46-51